Pengaruh Reputasi, E-Recruitment, dan Lingkungan Kerja Terhadap Minat Melamar Pekerjaan oleh Generasi Milenial di Kabupaten Toraja Utara - Natasya Jesica Putri1; Astriwati Biringkanae (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
The purpose of the study was to determine whether there is an effect of Reputation, E- recruitment, and Work Environment on Interest in Applying for Jobs by the Millennial Generation in North Toraja Regency. The data collection procedure of this research is Quantitative method using Multiple Linear Regression method and processed using SPSS This research was conducted around North Toraja, with a sample size of 100 respondents. The results of the calculation with the t test on the Reputation variable t count> t table with a value of (2.947) > (1.98498), on the E-recruitment variable t count> t table with a value of (4.014) > (1.98498), and on the Work Environment variable t count> t table with a value of (3.624) > (1.98498). The conclusion of this study is that Reputation, E-recruitment, and Work Environment have a positive and significant effect on Job Application Interest in the millennial generation in North Toraja Regency.